High-powered electric motorcycle integrated performance studies - Flanagan, Louis (2022)
Electric vehicles and low carbon technology are currently at the forefront of research due to the need to rapidly reduce global carbon emissions. Significant effort has been invested into the improvement of electric cars but comparatively little for electric motorcycles, especially high-performance electric motorcycles.